Does the characteristics of regional government and complexity affect on the disclosure regional financial statements? - Pancawati Hardiningsih; Indira Januarti; Ceacilia Srimindarti; Rachmawati Meita Oktaviani (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2019)
This study aims to analyze the factors that influence the level disclosure of Regional Government Financial Statements. The sample of this study were 101 local government financial statements at Indonesia in 2016-2018. This study uses multiple regression analysis. These results provide that regional wealth, government size, and the number of regional apparatus working units had a significant positive effects on the level of disclosure of Regional Government Financial Statements (RGFS). Whereas the level of dependency and the legislative had no effect on the level of disclosure of RGFS. Not all regional governments make disclosures based on RGFS by referring to new Government Regulation. This study uses a disclosure index that is considered to have an equal weight, and inappropriate use of proxies results in inappropriate analysis of the results showing the performance of local governments. It is expected that the future study is able to use the level of disclosure required RGFS based on the latest GAS accrual basis that began to be applied by all local governments in 2015, then need to give weight to items disclosed in the financial statements.